Multidisciplinary consensus recommendations from a European network for the diagnosis and practical management of patients with incontinentia pigmenti. (17th July 2020) - Bodemer, C.; Diociaiuti, A.; Hadj‐Rabia, S.; Robert, M.P.; Desguerre, I.; Manière, M.‐C.; de la Dure‐Molla, M.; De Liso, P.; Federici, M.; Galeotti, A.; Fusco, F.; Fraitag, S.; et al.
Abstract: Background: Incontinentia pigmenti (IP) is a rare multisystemic X‐linked dominant genetic disorder characterized by highly diagnostic skin lesions. The disease can be misdiagnosed in infants, and complications affecting the eyes and/or the brain can be severe. Our objective was to highlight the urgency of an appropriate diagnosis and management strategy, as soon as the first symptoms appear, and the need for a well‐codified monitoring strategy for each child. Methods: An in‐depth literature review using a large number of databases was conducted. The selection criteria for articles were literature review articles on the disease, case series and retrospective studies based on the disease, clinical studies (randomized or not) on treatment, articles discussing patient care and management (treatment, diagnosis, care pathways), and recommendations. The research period was from 2000 until 2018. A group of multidisciplinary experts in IP management was involved, issued from different healthcare providers of the European Network for Rare Skin Diseases (ERN‐Skin). The final recommendations have been submitted to two patient representative associations and to a general practitioner and a neonatal specialist prior to their finalization. Results and conclusion: The diagnosis of IP must be promptly performed to detect potential extracutaneous manifestations, thus allowing the timely implementation of specific therapeutic and monitoring strategies. Eye involvement can be a therapeutic urgency, and central nervous system (CNS) involvement requires a very rigorous long‐term follow‐up. Assessments and patient support should take into account the possible co‐occurrence of various symptoms (including motor, visual and cognitive symptoms).